Dietary phytochemical index and the risk of cancer: A systematic review and meta-analysis - Hamid Ahmadirad; Morteza Omrani; Nikoo Azmi; Amir Hesam Saeidian; Mitra Kazemi Jahromi; Hanifeh Mirtavoos-Mahyari; Mahdi Akbarzadeh; Farshad Teymoori; Hossein Farhadnejad; Parvin Mirmiran (PLoS ONE, 2025)
Background Recently, the association between dietary phytochemical index (DPI) and the risk of cancer has been the focus of researchers, however, this possible association has not been fully understood. The current meta-analysis aimed to assess the relationship between DPI and the risk of cancers. Methods A literature search by the main keywords such as “dietary phytochemical index”, “DPI”, and “cancer” was completed using Scopus, PubMed, and Web of Science up to December 2024 and references of retrieved relevant articles. Observational studies examining the association between the DPI and the risk of cancers were included. The reported odds ratio (OR) with a 95% confidence interval (CI) for each study was converted into log OR, and their standard deviation was calculated. Then to compute the pooled OR, the random-effects model with inverse variance weighting method was performed. Results Nine case-control studies were included in the present meta-analysis. The sample size ranged from 120 to 851 with an age range from 18 to 75 years. The pooled results indicate an inverse association between DPI and the risk of all cancers (OR: 0.40; 95% CI: 0.29–0.54, I2 = 0.00%; P-value < 0.001). Also, subgroup analysis indicated that higher a DPI score is related to the decreased risk of breast cancer (OR: 0.38; 95% CI: 0.26–0.55, I2 = 0.00%; P-value < 0.001) and pooled non-breast cancer including glioma, prostate, and colorectal cancers (OR: 0.43; 95% CI: 0.27–0.71, I2 = 0.00%; P-value = 0.001). Conclusions The results of the current meta-analysis revealed that the higher DPI score is associated with a decreased odds of cancers. Large-scale cohort studies are recommended to validate the findings presented in the current study.